2001
DOI: 10.1074/jbc.m102458200
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin (LA) Stimulates Milk β-1,4-Galactosyltransferase I (β4Gal-T1) to Transfer Glucose from UDP-glucose to N-Acetylglucosamine

Abstract: ␤-1,4-Galactosyltransferase 1 (Gal-T1) transfers galactose (Gal) from UDP-Gal to N-acetylglucosamine (GlcNAc), which constitutes its normal galactosyltransferase (Gal-T) activity. In the presence of ␣-lactalbumin (LA), it transfers Gal to Glc, which is its lactose synthase (LS) activity. It also transfers glucose (Glc) from UDPGlc to GlcNAc, constituting the glucosyltransferase (Glc-T) activity, albeit at an efficiency of only 0.3-0.4% of Gal-T activity. In the present study, we show that LA increases this act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 33 publications
4
104
2
Order By: Relevance
“…HFRC1 is the first UDP-Glc transporter to be reported in a mammal, although the physiological significance of UDPGlc transport in the Golgi apparatus is obscure. Possibly, it is involved in some glycosylation process in the Golgi apparatus, such as the addition of O-linked glucose (34) or the glucosyltransferase reaction by ␤4GalT1 in the presence of ␣-lactalbumin (35). On the other hand, we found that HFRC1 transported GDP-Man alone in the yeast, not in the mammalian cells.…”
Section: Discussionmentioning
confidence: 51%
“…HFRC1 is the first UDP-Glc transporter to be reported in a mammal, although the physiological significance of UDPGlc transport in the Golgi apparatus is obscure. Possibly, it is involved in some glycosylation process in the Golgi apparatus, such as the addition of O-linked glucose (34) or the glucosyltransferase reaction by ␤4GalT1 in the presence of ␣-lactalbumin (35). On the other hand, we found that HFRC1 transported GDP-Man alone in the yeast, not in the mammalian cells.…”
Section: Discussionmentioning
confidence: 51%
“…The 1194-bp (397 amino acids) ORF of b3Gn-T8 encoded a typical type II membrane protein, the same as in other b3Gn-Ts, consisting of an N-terminal cytoplasmic domain of 4 residues, a transmembane segment of 19 residues, and a stem region and a putative catalytic domain of 374 residues. A comparison of the amino acid sequence with that of other b3-glycosyltransferases revealed that this enzyme lacks the first aspartic acid of the DXD motif, identified as one of the b3Gn-T motifs and a divalent cationbinding site by a crystallization study on other glycosyltransferases [27,28]. Though b3Gn-T8 has an incomplete DXD motif, a divalent cation, Mn 2+ , is essential for the enzymatic activity like for other members of the family (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…b3Gn-T8 has QDD in its amino acid sequence instead of the DDD motif conserved in the other b3Gn-T members. It has been reported that the third aspartic acid in the DXD sequence in b4Gal-T1 binds to divalent metal ions [28]. b3Gn-T8 showed an absolute requirement for divalent metal ions, such as Mn 2+ , and the optimum concentration of Mn 2+ was between 2.5 and 10 mM.…”
Section: Determination Of Glycosyltransferase Activity and Substratementioning
confidence: 99%
“…2A) (25). The crystal structure of the bovine ␤4GalT1 has already been reported (24,27,28). The DXD motif is a Mn 2ϩ -binding site, and the other two motifs expose the surface of the catalytic pocket.…”
Section: Identification Of the Drosophila Proteoglycan ␤14-mentioning
confidence: 99%